Disorder or a new order: How climate change affects phenological variability. Issue 1 (5th October 2022) - Stemkovski, Michael; Bell, James R.; Ellwood, Elizabeth R.; Inouye, Brian D.; Kobori, Hiromi; Lee, Sang Don; Lloyd‐Evans, Trevor; Primack, Richard B.; Templ, Barbara; Pearse, William D.
Abstract: Advancing spring phenology is a well documented consequence of anthropogenic climate change, but it is not well understood how climate change will affect the variability of phenology year to year. Species' phenological timings reflect the adaptation to a broad suite of abiotic needs (e.g., thermal energy) and biotic interactions (e.g., predation and pollination), and changes in patterns of variability may disrupt those adaptations and interactions. Here, we present a geographically and taxonomically broad analysis of phenological shifts, temperature sensitivity, and changes in interannual variability encompassing nearly 10, 000 long‐term phenology time series representing more than 1000 species across much of the Northern Hemisphere. We show that the timings of leaf‐out, flowering, insect first‐occurrence, and bird arrival were the most sensitive to temperature variation and have advanced at the fastest pace for early‐season species in colder and less seasonal regions. We did not find evidence for changing variability in warmer years in any phenophase groups, although leaf‐out and flower phenology have become moderately but significantly less variable over time. Our findings suggest that climate change has not to this point fundamentally altered the patterns of interannual phenological variability.